2020
DOI: 10.1021/acsinfecdis.0c00432
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Treatment-Naive Gut Microbiome in Newly Diagnosed Hepatitis C Virus Infection

Abstract: Gut microbiota dysbiosis has been linked to many heath disorders including hepatitis C virus (HCV) infection. However, profiles of the gut microbiota alterations in HCV are inconsistent in the literature and are affected by the treatment regimens. Using samples collected prior to treatment from newly diagnosed patients, we characterized the gut microbiota structure in HCV patients as compared to healthy controls. Treatment-naive HCV microbiota showed increased diversity, an increased abundance of Prevotella, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 48 publications
0
26
2
Order By: Relevance
“…In contrast with the previously published literature, Sultan et al demonstrated an increased gut microbiota diversity in treatment-naïve patients with HCV infection compared to healthy controls, with a higher abundance of Prevotella, Succinivibrio, Collinsella, Faecalibacterium, Coriobacteriaceae, Catenibacterium, Megasphera, Mitsuokella multacida, and Ruminococcaceae, and a lower abundance of Bacteroides, Dialister, Alistipes, Bilophila, Streptococcus, and Enterobacteriaceae [39].…”
Section: Hepatitis C Virus (Hcv)contrasting
confidence: 59%
“…In contrast with the previously published literature, Sultan et al demonstrated an increased gut microbiota diversity in treatment-naïve patients with HCV infection compared to healthy controls, with a higher abundance of Prevotella, Succinivibrio, Collinsella, Faecalibacterium, Coriobacteriaceae, Catenibacterium, Megasphera, Mitsuokella multacida, and Ruminococcaceae, and a lower abundance of Bacteroides, Dialister, Alistipes, Bilophila, Streptococcus, and Enterobacteriaceae [39].…”
Section: Hepatitis C Virus (Hcv)contrasting
confidence: 59%
“…HCV is considered one of the major etiological agents of hepatitis, which results in severe liver complications, including cirrhosis, HCC, and it may even lead to liver failure and death [ 125 ]. There is little published literature regarding the impact of HCV infection on gut microbiota [ 97 , 121 , 134 , 135 , 136 , 137 , 138 , 139 ]. Additionally, the mechanistic understanding of how microbial dysbiosis participates in the disease’s progression is not completely addressed.…”
Section: Gut Microbiota Dysbiosis In Hcvmentioning
confidence: 99%
“…This HCV-associated depletion of the gut microbiota diversity was mitigated after treatment with antiviral drugs [ 97 ]. In contrast, a recent study reported a lower microbial diversity in healthy adults as compared to treatment of naïve newly diagnosed HCV patients, which illustrates the impact of the treatment as a confounding factor in microbiome studies [ 137 ]. Additionally, this difference in HCV-associated diversity may be attributed to different cohort’s ethnicities, therapeutic factors, and different disease stages.…”
Section: Gut Microbiota Dysbiosis In Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut contains a large, complex microbial community that has much more genetic material than the total human genome[ 1 ]. Gut microbiota (GM) acts as a major determinant of complex bidirectional communication between the gut and brain to maintain intestinal homeostasis and host health[ 2 , 3 ]. However, gastrointestinal tract bacteria produce several enzymes, metabolites, and cellular components that can contribute to many disorders such as liver disease[ 3 ], diabetes mellitus[ 4 ], inflammatory bowel disease[ 5 ], irritable bowel syndrome[ 6 ], obesity[ 7 ], colorectal cancer[ 8 ], and mental illness[ 9 ].…”
Section: Introductionmentioning
confidence: 99%